2011
DOI: 10.1080/00380768.2011.591284
|View full text |Cite
|
Sign up to set email alerts
|

Using different versions of the Rothamsted Carbon model to simulate soil carbon in long-term experimental plots subjected to paddy–upland rotation in Japan

Abstract: We validated the Rothamsted Carbon (RothC) model against 14 experimental plots subjected to different paddy-upland rotation patterns, including continuous paddy rice cropping and different periods (short, medium, and long term) of upland conversion, in Akita prefecture, northern Japan. We ran the model using the original version of the RothC model, the paddy-soil version of the RothC model (which uses a reduced carbon decomposition rate), and alternating the use of the original and the paddy-soil versions for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Accumulation of organic matter (i.e., carbon and nitrogen) in paddy soils is important from the perspective of responding to climate change and maintaining crop productivity (details are described in Takakai et al 2019, in this issue). Long-term application of organic matter to paddy fields increases carbon storage in the soil (e.g., Cheng et al 2016;Shirato, Yagasaki, and Nishida 2011;Sumida, Kato, and Nishida 2005;Yokozawa et al 2010). In order to quantitatively evaluate the effects of long-term application of organic matter on soil carbon storage, it is effective to use fields with long-term experiments on continuous cropping that have been conducted in various parts of Japan (Kanamori 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulation of organic matter (i.e., carbon and nitrogen) in paddy soils is important from the perspective of responding to climate change and maintaining crop productivity (details are described in Takakai et al 2019, in this issue). Long-term application of organic matter to paddy fields increases carbon storage in the soil (e.g., Cheng et al 2016;Shirato, Yagasaki, and Nishida 2011;Sumida, Kato, and Nishida 2005;Yokozawa et al 2010). In order to quantitatively evaluate the effects of long-term application of organic matter on soil carbon storage, it is effective to use fields with long-term experiments on continuous cropping that have been conducted in various parts of Japan (Kanamori 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, predictive power of RothC_p application for paddy fields needs further validation and refinement, as this subversion of RothC model, employing additional parameters to adjust SOC decomposition rate under submerged and drained yet rather moist soil conditions by simple tuning, has been tested with data from only a limited numbers of longterm field experiments at this stage (Shirato and Yokozawa, 2005;Shirato et al, 2011). As paddy fields have been holding one of the largest area is among all land-use types in agricultural lands in Japan, even relatively small changes in prediction on the rate of SOC stock change per unit area basis in this land-use category may exert large impact on overall figure of country level estimation of SOC stock change.…”
Section: Uncertaintiesmentioning
confidence: 99%
“…In order to support the decision making of policy makers at local or central governmental level and implementation of SOC sequestration on agricultural lands, it is essential to develop measures that enable them to provide a reliable estimation on future potential of SOC sequestration at large spatial scale. So far, previous studies have demonstrated that application of currently available process-based models of SOC turn-over is an effective approach to estimate temporal changes in SOC stock over several decades or centuries (Jenkinson et al, 1990;Kelly et al, 1997;McGill, 1996;Shirato and Yokozawa, 2005;Shirato et al, 2004;Skjemstad et al, 2004). In many of those studies, validation of the model was conducted based on observed changes in SOC stock in long-term field experiments, in which the rate of organic matter application to soils or soil initial conditions, key parameters determining SOC stock change, have had been known or well identified.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the effects of poultry manure compost and swine manure compost on soil N fertility in paddy-upland rotation have yet to be elucidated. It was reported that different versions of the Rothamsted Carbon model could simulate soil carbon dynamics in paddyupland rotations (Shirato et al 2011). The development of a dynamic model of available soil N in paddy-upland rotation would greatly improve the understanding and management of soil N fertility.…”
Section: Issues and Perspectivesmentioning
confidence: 99%